ANALISIS REGRESI DATA PANEL PADA PERTUMBUHAN EKONOMI DI NEGARA – NEGARA ASIA - Aris Munandar (Universitas Indo Global Mandiri)
Panel data regression analysis is a combination of data time series and cross section data. The use of panel data can explain two kinds of information that are information between units and time. The purpose of this study is to determine the factors affecting Economic Growth in Asian Countries. Cross section data comprising 8 countries and time series from year 1990 to 2016 are used. The result of the study suggests that the best regression model estimation is the fixed effect model. With this model, 24.57% of the variability of Economic Growth can be explained by Tax variable, Government Debt, Household Consumption and Loan Interest Rate. The estimation of the panel regression equation is Y = 5.719698 - 2.54E-14 PAJAKit -3.57E-15 HUTANGIT + 6.52E-15 CONSUMPTES - 0.043112 CREDITITE. Tax, Government Debt and Loan Interest Rates have a negative and significant effect on economic growth, while Household Consumption has a significant positive effect on economic growth.Key words : Economic Growth, Taxes, Government Debt, Household Consumption, Loan Interest Rate